2003
DOI: 10.1126/science.1081634
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Infrared Spectrum of the Protonated Water Dimer

Abstract: The protonated water dimer is a prototypical system for the study of proton transfer in aqueous solution. We report infrared photodissociation spectra of cooled H+(H2O)2 [and D+(D2O2] ions, measured between 620 and 1900 wave numbers (cm-1). The experiment directly probes the shared proton region of the potential energy surface and reveals three strong bands below 1600 cm-1 and one at 1740 cm-1 (for H5O2+). From a comparison to multidimensional quantum calculations, the three lower energy bands were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
380
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(404 citation statements)
references
References 27 publications
17
380
0
7
Order By: Relevance
“…Incidentally, for the present type of symmetric protonbonded systems, the harmonic MP2/cc-pVTZ result (961 cm versus 697 cm À1 (observed band b') [1] and the proton-bonded dimethyl ether dimer with 823 cm À1 (MP2/cc-pVTZ, G. von Helden, personal communication) versus 810 cm À1 observed. [14] An alternative method with full coupling and full anharmonicity is the calculation of the IR spectra as the Fourier transform (FT) of the dipole autocorrelation function from trajectories generated by ab initio MD.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Incidentally, for the present type of symmetric protonbonded systems, the harmonic MP2/cc-pVTZ result (961 cm versus 697 cm À1 (observed band b') [1] and the proton-bonded dimethyl ether dimer with 823 cm À1 (MP2/cc-pVTZ, G. von Helden, personal communication) versus 810 cm À1 observed. [14] An alternative method with full coupling and full anharmonicity is the calculation of the IR spectra as the Fourier transform (FT) of the dipole autocorrelation function from trajectories generated by ab initio MD.…”
mentioning
confidence: 99%
“…+ in the 500-2000 cm À1 region (in which the modes of the bridging proton are expected) by Asmis et al [1] has raised questions [2,3] about the assignment [4] of the observed bands and stimulated more experimental work. [3,5,6] Most recently, infrared predissociation (IRPD) spectroscopy has been applied to the complex of H 5 O 2 + with Ar, [5,6] and the spectrum obtained shows some differences to that obtained by IRMPD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these successful applications of an FEL to IRMPD spectroscopy of molecular ions, more sophisticated mass spectrometers have been installed at FEL facilities, most notably tandem mass spectrometers 57,58 and Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometers. [59][60][61][62] Ion trapping in combined magnetic and electric fields coupled with FT-ICR mass analysis leads to unparalleled mass resolving power and mass accuracy, and a multitude of ion formation, manipulation and isolation techniques have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The IR spectrum of gas phase H 5 O 2 1 has only recently been measured. 16 Car-Parrinello molecular dynamics (CPMD) 17,18 provides a unique possibility to study the effect of the crystalline environment on the structure and dynamics of H 5 O 2 1 when one accepts the limited accuracy of density functional theory (DFT), see ref. 19 for a recent example.…”
Section: Introductionmentioning
confidence: 99%